GASTROINTESTINAL HELMINTHOSES: PREVALENCE AND ASSOCIATED RISK FACTORS IN SMALL RUMINANTS OF DISTRICT KOHAT, PAKISTAN - A. Rashid; M. N. K. Khattak; M. F. Khan; S. Ayaz; A. U. Rehman (Journal of Animal and Plant Sciences, 2016)
Gut contents of 500 freshly slaughtered small ruminants (300 goats and 200 sheep) were studied using floatation and sedimentation methods followed by direct microscopic examination aims to investigate the prevalence of gastrointestinal tract helminthes in small ruminants of district Kohat, Khyber Pakhtunkhwa Pakistan during March-November 2013. Overall, 45.6% samples were found positive for helminthes parasites comprising nematodes (23.0%), cestodes (22.4%) and trematodes (0.2%). The prevalence of GIT helminthes was higher in goats compared to sheep (49.0% vs. 40.5%), but the same was statistically not significant (p>0.05). Gender-wise prevalence of GIT helminthes in goats and sheep was also not significant (P>0.05) whereas prevalence of GIT helminthes was significantly higher (p<0.05) in young compared to adult sheep, however, the phenomenon was not observed in goats. Prevalence of GIT helminthes was significantly different (P<0.0001) across different seasons and GIT parts of host animals.
Keywords: Gastrointestinal helminthoses; small ruminants; goats; sheep; Pakistan